Facial affect perception and mentalizing abilities in female patients with persistent somatoform pain disorder. (7th January 2014) - Schönenberg, M.; Mares, L.; Smolka, R.; Jusyte, A.; Zipfel, S.; Hautzinger, M.
Abstract Background Numerous studies have demonstrated a robust link between alexithymic traits and somatic complaints in patients suffering from psychosomatic disorders, while less is known about disease‐related impairments in the processing of affective social information. Deficits in emotion recognition can lead to misinterpretations of social signals and induce distress in interpersonal interactions. This, in turn, might contribute to somatoform symptomatology in affected individuals. The aim of the present study was to investigate basal facial affect recognition as well as higher‐order cognitive mind‐reading skills in order to further clarify the association between alexithymia and the processing of social affective information in a homogenous sample of patients suffering from somatoform pain. Methods We employed a series of animated morph clips that gradually displayed the onset and development of the six basic emotional expressions to investigate facial affect perception in a female sample of patients diagnosed with persistent somatoform pain disorder (PSPD) and matched healthy controls. In addition, all participants were presented with the Movie for the Assessment of Social Cognition to explore mind‐reading abilities. Results Specifically impaired mentalizing skills and increased alexithymic traits were observed in PSPD, while emotional facial expression recognition appeared to be intact in these patients. Conclusions PSPD subjects tend to overattribute inappropriate affective states to others, which could be the consequence of the inability to adequately experience and express their own emotional reactions. This cognitive bias might lead to the experience of poor psychosocial functioning and has the potential to negatively impact the course and outcome of this psychopathology.